Prevalence of anemia in pregnant women and its association with birth outcomes in Bhimpur block, Betul district, Madhya Pradesh - Upadhayay, Pranjal (International Journal of Research in Medical Sciences, 2025)
Background: Anemia Pregnant is an important and widely public health issue in the world and a leading cause of maternal morbidity and poor birth outcomes especially in low resources and tribal nations. Methods: The sampling was done in the Bhimpur block of Betul district, Madhya Pradesh wherein 300 pregnant women were selected, and the study was conducted to estimate the prevalence and severity of anemia as well as its relationship with low birth weight (LBW) and preterm birth as adverse pregnancy outcomes. Results: The hemoglobin level was measured with the help of hemoglobin meter, and anemia was determined according to WHO classification. It has been found that anemia was prevalent (64.7%), and most of the cases were mild (38.3%), moderate (24.7%), and only a small proportion of severe cases was observed (1.7%). LBW was found (27.5%) in a higher rate of 39.2% in anemic mothers and 11.8% in non-anemic mothers (p < 0.001). Anemia also revealed a dose-response relationship, with the higher the anemia, the higher the number of preterm births (p = 0.004), i.e., it is also found to be significant between the anemic and non-anemic women, with preterm births being higher in the former. Conclusions: The results indicate that a continuously high prevalence of anemia in tribal pregnant women and its close relationship with unfavorable perinatal outcomes. Enhancement of culturally sensitive nutrition education, antenatal care and program execution through such initiative as Anemia Mukt Bharat is essential in the enhancement of maternal and new-born health.